Active involvement of students in co-curriculum (sports) versus generic skills - Rozali, Mohd Zulfadli; Puteh, Saifullizam (Publications International Lahore, Pakistan, 2017)
The active involvement of students in sports activities is viewed from different levels of achievement beginning with the national representation of the residential colleges, faculties, and universities in prestigious sporting events at international levels. The skills that are developed through extra-curricular activities are generic skills. The involvement of students in co-curricular activities can help to shape their generic skills, thus leading to self-promotion in the workplace. Therefore, the purpose of this research was to examine the enhancement of generic skills among engineering and technical students of UTHM who are actively involved in co-curricular activities (sports). This study will focus on identifying the factors of involvement, the level of application among students, and the perceptions of the students through their active involvement in extra-curricular activities (sports). A survey was conducted using a quantitative approach. A general questionnaire, which was designed to fulfil the objectives and to answer the research questions for this study, was distributed to 213 engineering and technical student athletes of UTHM who are actively involved in co-curricular activities (sports). It was found that the engineering and technical student athletes of UTHM agreed that their active involvement in extra-curricular activities (sports) was due to interpersonal, intrapersonal and structural factors. The results showed that out of seven generic skills, three constructs of generic skills, namely communication, teamwork and management, demonstrate a high level of application through active involvement in extra-curricular activities (sports). These findings may also help the university to focus on the development of generic skills in engineering and technical students through co-curricular activities (sports) in addition to producing athletes who are able to create a name for the university at national or international levels